أثر المخاطر الاستثمارية في ربحية شركات التأمين التعاوني (2020- دراسة قياسية عن الشركة التعاونية للتأمين السعودية للمدة ( 2: The impact of investment risks on the profitability of cooperative insurance companies, a standard study on the Saudi Tawuniya Insurance Company during (2006-2020) - .شرقي محمد; حمدي معمر (Journal of North African Economies, 2025)
The aim of the study was to identify and most importantly identify cooperative insurance companies, highlighting the various investment risks to which these companies are exposed. The study also attempted to measure the impact of some of these investment risks on the profitability of cooperative insurance companies using the realized rate of investment return, which was applied to the Saudi Cooperative Insurance Company for the period (2006-2020), using the ARDL (Autoregressive-Distributed Lag) model. The study found a negative impact on both inflation risk and exchange rate risk on investment return and no market risk effect.